Aptamers and Their Applications in Nanomedicine. Issue 20 (11th February 2015) - Sun, Hongguang; Zu, Youli
<x xml:space="preserve">Abstract</x> Aptamers are composed of short RNA or single‐stranded DNA sequences that, when folded into their unique 3D conformation, can bind to their targets with high specificity and affinity. Although functionally similar to protein antibodies, oligonucleotide aptamers offer several advantages over protein antibodies in biomedical and clinical applications. Through the enhanced permeability and retention effect, nanomedicines can improve the therapeutic index of a treatment and reduce side effects by enhancing accumulation at the disease site. However, this targets tumors passively and, thus, may not be ideal for targeted therapy. To construct ligand‐directed "active targeting" nanobased delivery systems, aptamer‐equipped nanomedicines have been tested for in vitro diagnosis, in vivo imaging, targeted cancer therapy, theranostic approaches, sub‐cellular molecule detection, food safety, and environmental monitoring. This review focuses on the development of aptamer‐conjugated nanomedicines and their application for in vivo imaging, targeted therapy, and theranostics.